A geometria escolar: uma análise dos estudos sobre o abandono de seu ensino - Pereira, Maria Regina de Oliveira (2001)
The objective of this work is to offer the possibility of better understand and also to recover the Geometry condition in the Ensino Fundamental and Ensino Médio (Primary and Secondary Teaching System) curricula. I have focused my research looking for justification for its abandon and from the existing literature inventory I describe some researches which give ideas about its situation. Such examples result in a repertoire composition in order to relate the focused works on n this subject and to be useful as a level for further researches